2019
DOI: 10.1002/jcp.28449
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA expression profile in human fibroblast premature senescence after repeated ultraviolet B irradiations revealed by microarray

Abstract: Circular RNA (circRNA) is a class of noncoding RNA that regulates the activity of microRNAs and gene expression. Altered circRNA expression is associated with human diseases. The present study profiled differentially expressed circRNAs in the ultraviolet B stress‐induced human fibroblast premature senescence (UVB‐SIPS) model, and assessed the role of circRNA_100797 in UVB‐SIPS. The UVB‐SIPS model was confirmed by ß‐galactosidase staining, cell viability CCK‐8 assay, and flow cytometric cell cycle distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Besides, in the model of the UVB stress-induced premature senescence (UVB-SIPS) of human fibroblasts, it was found that the overexpression of miR-23a-5p reduced cellular proliferation and accelerated a cell cycle arrest. At the same time, in UVB-SIPS fibroblasts it had an opposite effect on the photoprotective circulatory RNA_100797, which acted as a sponge of miR-23a-5p [ 207 ].…”
Section: The Role Of Mirnas In Dermal Photoagingmentioning
confidence: 99%
“…Besides, in the model of the UVB stress-induced premature senescence (UVB-SIPS) of human fibroblasts, it was found that the overexpression of miR-23a-5p reduced cellular proliferation and accelerated a cell cycle arrest. At the same time, in UVB-SIPS fibroblasts it had an opposite effect on the photoprotective circulatory RNA_100797, which acted as a sponge of miR-23a-5p [ 207 ].…”
Section: The Role Of Mirnas In Dermal Photoagingmentioning
confidence: 99%
“…Circular RNA (circRNA) is a type of endogenous RNA that forms a covalently closed continuous loop structure without a 5 -cap or a 3 -poly A tail (Wang et al, 2019c;Wei et al, 2020). Owing to its structure, circRNA is more stable than linear RNA and can be resistant to exonucleolytic RNA decay (Si et al, 2019;Liu T. et al, 2020). CircRNA is involved in the regulation of many diseases by interacting with disease-associated microRNA (miRNA) as a competing endogenous RNA (ceRNA) (Wang et al, 2018;Zhang Y. et al, 2019;Li H. et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Some roles of these microRNA have been revealed, such as the miR-125a-5p can affect cell migration and modulate sensitivity to ionizing radiation [32], the miR-143-3p increases in exosome-like EVs from irradiated whole blood samples and contributes to early stages of radiation-induced genomic instability [33,34], the miR-199a-5p works as a novel and unique regulator of radiation induced-autophagy [35], and the miR-455-3p regulates cell growth, metastasis, and glycolysis in hepatocellular carcinoma [36]. The miR-23a-5p blocks the effect of the acceleration of cell proliferation and alleviation of cell cycle arrest [37], and the miR-1894-3p works as an important antimetastatic miRNA in lung metastasis [38].…”
Section: Discussionmentioning
confidence: 99%